RELATIONSHIP BETWEEN DIET AND LIPID PROFILE OF HEALTHY INDIVIDUALS (The Research of Medical Science Review, 2024)
A community based cross-sectional study was conducted to explore a possible link of diet and lipid profile among the healthy female adults (N=100) aged 20-60 years of District Peshawar. Socio-demographic, anthropometric, dietary and biochemical data were collected from the concerned females. Socio-demographic data indicates that majority of the subjects were educated, married, unemployed. Anthropometric measurements indicate that 34% of the female were of normal weight, 7% were underweight and 59% were overweight and obese. Only 20% of the subjects had normal waist circumference. Serum samples investigated for lipid profile indicate that TG, TC, VLDL and LDL were significantly (P<0.05) correlated with weight, WC and BMI. HDL was negatively correlated with BMI, weight and WC. Mean TC, LDL, TG and VLDL were significantly different while mean HDL was non-significantly different in all groups of BMI. Moreover, on the basis of WC, mean TG, TC, HDL and LDL was significantly (P<0.05) different in at risk and normal groups. No statistical difference (P>0.05) was observed among the mean intake of calories, fats, protein and CHO of at risk and normal individuals. TC and LDL were positively correlated with fats and proteins while TG and HDL were negatively correlated (P>0.05) with fats. Milk and milk products, eggs, beverages and fats consumed higher in at risk women while fruits, vegetables, and nuts were highly consumed by normal subjects. The study provides base line information about nutritional status, dietary intake and lipid profile of the individuals of this region.